Gestão escolar no estado de São Paulo: perspectiva democrática ou modelo gerencial? uma análise a partir do relatório dos estudos do SARESP (2010 a 2012) - Oliveira, Tânia Cabral de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The school management has been the subject of discussion in political and academic by the centrality that has education in contemporary media. After the military regime as part of the process of democratization of society, democratic management education was established as guiding principle of education systems and schools by the Federal Constitution of 1988 and regulated by the Law of Guidelines and Bases of Education n ° 9.394/96, leaving the responsibility of Education Systems to establish the elements of achievement according to their peculiarities, since the community participated in drafting the proposal and the Pedagogical Councils were established to encourage participation. Because of changes in the political and economic environment, the democratic management of education was implemented taking into account the decisions of international bodies, losing their transformative potential of relations in society, and participation and autonomy, the main elements of achievement, became management techniques in management or co-management model. In São Paulo, the Basic Regimental Standards established the principle of democratic management and prepared the way for this mischaracterization occurred. Because of grammars that are steeped in Brazilian social practices, clientelism and patronage, bureaucracy that leads to authoritarianism and the nature of the liberal democratic state, the principle of democratic management encounters many obstacles to consolidate and lost their transformative potential. The present study aimed to determine whether, in the opinion of the school community, democratic management has consolidated your participation in school and in decision making in schools. We used data from the Study reports of SARESP the years 2010 to 2012, bringing together the answers of students, parents, teachers, principals and coordinators to questionnaires applied context before each issue of assessment for this,. These data are...

A gestão escolar tem sido alvo de discussões em meios políticos e acadêmicos pela centralidade que possui a educação na contemporaneidade. Após o regime militar, como parte do processo de democratização da sociedade, a gestão democrática da educação foi estabelecida como princípio norteador dos sistemas de ensino e das escolas pela Constituição Federal de 1988 e regulamentada por meio da Lei de Diretrizes e Bases da Educação n° 9.394/96, deixando sob a responsabilidade dos Sistemas de Ensino o estabelecimento dos elementos de consecução de acordo com suas peculiaridades, desde que a comunidade participasse da elaboração da Proposta Pedagógica e os Conselhos fossem estabelecidos para fomentar a participação. Em virtude das mudanças no cenário político e econômico, a gestão democrática da educação foi implementada levando-se em consideração as determinações de organismos internacionais, perdendo seu potencial transformador das relações na sociedade, sendo que a participação e a autonomia, seus principais elementos de consecução, passaram a ser técnicas de gestão no modelo gerencial ou de gestão compartilhada. No estado de São Paulo, as Normas Regimentais Básicas estabeleceram o princípio da gestão democrática e prepararam o caminho para que esta descaracterização ocorresse. Em virtude das gramáticas que estão impregnadas nas práticas sociais brasileiras, o clientelismo e o patrimonialismo, da burocracia que leva ao autoritarismo e da natureza do estado liberal democrático, o princípio da gestão democrática encontra muitos obstáculos para se consolidar, perdendo assim seu potencial transformador. O presente trabalho teve por objetivo verificar se, na opinião da comunidade escolar, a gestão democrática tem se consolidado pela sua participação na escola e na tomada de decisão no âmbito escolar. Para isso, foram utilizados os dados do Relatório dos Estudos do SARESP dos anos...
Keywords: Escolas - Organização e administração - 2010-2012; Educação – São Paulo (Estado); Comunidade e escola; Gestão democrática; Educação - Finalidades e objetivos; Educational administration